For a random walk,
$$y_t = \sum_{s=1}^{t} u_s$$
you can write
$$y_{t+1} = y_{t} + u_{t+1}$$
which shows that the distribution of $y_{t+1}$ only depends on the before last step and not the entire history.
More clearly we can show it by writing out the expression for the distribution of $y_{t+1}$
$$y_{t+1} \sim N(y_t,\sigma^2)$$
and this distribution of the future state $y_{t+1}$ only depends on the present state $y_{t}$
For your case,
You can rewrite your $x_t$ in terms of this random walk. To simplify this I use a transformed/shifted variable the $z_t = x_t+1$
$$z_t = 1+x_{t} = 1 + \frac{u_t}{ \sum_{s=1}^{t-1} u_s} = \frac{\sum_{s=1}^{t-1} u_s}{ \sum_{s=1}^{t-1} u_s} + \frac{u_t}{ \sum_{s=1}^{t-1} u_s} = \frac{y_t}{y_{t-1}}$$
This $z_{t}$ is not memoryless. Intuitively, it depends on $y_t$ and also the previous step $y_{t-1}$.
We can make this more clear by deriving the distribution of $z_{t+1}$ and show that you need more than only $z_{t}$ and $u_{t+1}$. Namely, you also need to know $y_{t-1} = \sum_{s=1}^{t-1} u_t $.
$$z_{t+1} = \frac{y_{t+1}}{y_{t}} = \frac{z_ty_{t-1} + u_{t+1}}{z_ty_{t-1}} = 1 + \frac{u_{t+1}}{z_ty_{t-1}}$$
For the same $z_t$, the $y_{t-1}$ can be different. Thus the distribution of $z_{t+1}$ does not solely depend on $z_{t}$, and also on the history of $z_t$ described by $y_{t-1}$.
$$z_{t+1} \sim N\left( 1,\frac{\sigma^2}{z_t^2} \cdot \frac{1}{y_{t-1}^2} \right)$$
The same can be argued for $x_t$ as for $z_t$.
$$x_{t+1} \sim N\left( 0,\frac{\sigma^2}{(x_t+1)^2} \cdot \frac{1}{y_{t-1}^2} \right)$$